2019
DOI: 10.1172/jci123557
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling ATPase BRG1 and PTEN are synthetic lethal in prostate cancer

Abstract: that BRG1 inhibition is a promising approach against PTENmutant prostate tumors in preclinical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 66 publications
6
60
0
Order By: Relevance
“…Most recently, two studies demonstrated that SMARCA4 was required for growth of prostatic adenocarcinoma cells 69,75 , as also confirmed by our results (Fig. 2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most recently, two studies demonstrated that SMARCA4 was required for growth of prostatic adenocarcinoma cells 69,75 , as also confirmed by our results (Fig. 2).…”
Section: Discussionsupporting
confidence: 91%
“…2). Localized PCa has previously been reported to show higher SMARCA4 and lower SMARCA2 expression than benign prostate tissue 69,[75][76][77] . We further report an overexpression of SMARCA4 in CRPC and especially in CRPC-NE, in contrast to lower expression in early PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the BRD protein BRG1, encoded by SMARCA4, is an ATPase subunit of the SWI/SNF complex that mobilizes nucleosomes (Griffin et al 2008, Medina & Sanchez-Cespedes 2008. Ding et al recently showed that increased BRG1 expression in PTEN-deficient PC cells led to chromatin remodeling into a configuration that drove a protumorigenic transcriptome (Ding et al 2019). They employed ATAC-seq in PTEN-deficient 22Rv1 PC cells to show that BRG1 knockdown led to a 60% reduction in open chromatin regions compared to BRG1-intact cells (Ding et al 2019).…”
Section: Bromodomain-containing Proteins and Chromatin Reprogramming mentioning
confidence: 99%
“…Ding et al recently showed that increased BRG1 expression in PTEN-deficient PC cells led to chromatin remodeling into a configuration that drove a protumorigenic transcriptome (Ding et al 2019). They employed ATAC-seq in PTEN-deficient 22Rv1 PC cells to show that BRG1 knockdown led to a 60% reduction in open chromatin regions compared to BRG1-intact cells (Ding et al 2019). They also showed that high BRG1 expression was associated with worse outcomes in PC patients with low PTEN expression (Ding et al 2019).…”
Section: Bromodomain-containing Proteins and Chromatin Reprogramming mentioning
confidence: 99%